Conocimiento desinteresado y ciencia americana : El Congreso Científico (1898-1916) (2011)
ABSTRACT: This article examines the Congreso Científico (Scientific Congress) that met between 1898 and 1916 as a means of international dialogue. It describes the meetings as a public space within the sphere of international relations. After showing how the initial creation was plural and not an extension of relations between states, the article demonstrates the way oficial interventions became increasingly apparent in its decisions, to the point of being incorporated into the imperial agenda of the United States. It also underlines how the declaration of sience's independence from politics competed with the demand for knowledge to be applied to the problems of American government and economy.